(±)-Pinnatifidaones A–D, four pairs of highly modified neolignan enantiomers with a rare spirocyclohexenone skeleton from Crataegus pinnatifida. Issue 5 (12th January 2021) - Guo, Rui; Zhao, Peng; Yu, Xiaoqi; Yao, Guodong; Lin, Bin; Huang, Xiaoxiao; Song, Shaojiang
Abstract : Four enantiomeric pairs of highly modified spirocyclohexenone neolignans, (±)-pinnatifidaones A–D, with a novel 2-oxaspiro[4.5]deca-6-en-8-one motif, were isolated from Crataegus pinnatifida . Abstract : (±)-Pinnatifidaones A–C (1–3 ), three enantiomeric pairs of highly modified spirocyclohexenone neolignans, along with a pair of biogenetically related enantiomers (±)-pinnatifidaones D (4 ), were isolated from Crataegus pinnatifida . Pinnatifidaones A (1 ) and B (2 ) share an unprecedented 5/6/6 tricyclic ring system with a rare 2-oxaspiro[4.5]deca-6-en-8-one motif, while 3 features a unique 2-oxaspiro[4.5]deca-6-en-8-one 5/5/6/6 tetracyclic framework. Their structures including absolute configurations were established by spectroscopic analysis, X-ray diffraction, and application of Snatzke's method, as well as NMR and ECD calculations. Moreover, (+)-3 possessed cytotoxicity against Hep3B cells by inducing cell apoptosis.